Molecular characterization and functional analysis of four β‐1, 4‐endoglucanases from the root‐lesion nematode Pratylenchus vulnus. (10th April 2014) - Fanelli, E.; Troccoli, A.; Picardi, E.; Pousis, C.; De Luca, F.
<x xml:space="preserve">Abstract</x> This study reports on the isolation and characterization of four different endoglucanases in the root‐lesion nematode Pratylenchus vulnus. The gene structures of two of these, Pv‐eng‐1 and Pv‐eng‐2, were fully determined, and Pv‐eng‐3 and Pv‐eng‐5 were partially sequenced. Spatial expression of Pv‐eng‐1, Pv‐eng‐2 and Pv‐eng‐5 was examined by in situ hybridization. Pv‐eng‐1 and Pv‐eng‐2 transcripts were localized in the subventral oesophageal glands, whilst the Pv‐eng‐5 transcript was localized in the intestine. Real‐time RT‐PCR showed that three of the four endoglucanases had the highest transcriptional level in adult males and females, thus demonstrating that adults are also parasitic in P. vulnus. Mixed stages of P. vulnus were treated with double‐stranded RNA (dsRNA) of Pv‐eng‐1 in order to study the effect of gene silencing (RNAi). Silencing Pv‐eng‐1 by dsRNA targeting of the carbohydrate‐binding module (CBM) resulted in a significant reduction (88–98%) of the transcript level, suggesting that P. vulnus is susceptible to RNAi. Furthermore, silencing P. vulnus showed a reduction (54%) in nematode reproduction on carrot minidiscs over a 5 week period. These results suggest that silencing of Pv‐eng‐1 may result in reduction of the ability of the nematode to locate and invade roots and, therefore, to establish and reproduce.